The predictive significance of fluctuations in early maternal sensitivity for secure base script knowledge and relationship effectiveness in adulthood. (October 2022) - Eller, Jami; Magro, Sophia W; Roisman, Glenn I; Simpson, Jeffry A
Attachment theory suggests that both the quality and consistency of early sensitive care should shape an individual's attachment working models and relationship outcomes across the lifespan. To date, most research has focused on the quality of early sensitive caregiving, finding that receiving higher quality care predicts more secure working models and better long-term relationship outcomes than receiving lower quality care. However, it remains unclear whether or how the consistency of early sensitive care impacts attachment working models and adult relationship functioning. In this research, we utilized data from the Minnesota Longitudinal Study of Risk and Adaptation to examine to what extent the quality (i.e., mean levels) and consistency (i.e., within-person fluctuations) in behaviorally coded maternal sensitive care assessed 7 times from 3 months to 13 years prospectively predicts secure base script knowledge and relationship effectiveness (i.e., interpersonal competence in close relationships) in adulthood. We found that larger fluctuations and lower mean levels of early maternal sensitivity jointly predict lower relationship effectiveness in adulthood via lower secure base script knowledge. These findings reveal that nonlinear models of early caregiving experiences more completely account for relationship outcomes across the lifespan, beyond what traditional linear models have documented. Implications for attachment theory and longitudinal methods are discussed.